A geografia das feiras de negócios e a dinâmica do setor agroalimentar brasileiro - Bauermann, Andressa Krieser (2024)
Brazilian agriculture is currently experiencing a period of deepening market integration, making it impossible to analyze in isolation from other sectors. As agricultural modernization advances, its influence extends beyond farming, and impacts other economic sectors. In this context, this dissertation explores how trade fairs shape the spatial, economic, and technological dynamics of Brazilian agribusiness. Given that this sector encompasses production, processing (industry), and services, this study provides a comprehensive perspective on the agricultural environment. Furthermore, trade fairs operating across various segments of the agri-food sector find favorable conditions in Brazil, as the country simultaneously serves as a producer of raw materials, a processor (agribusiness sector), and a well-established market for commercialization. Accordingly, the central hypothesis of this dissertation is that trade fairs serve as key mechanisms for both the creation and dissemination of technology within the sector, particularly in relation to cutting-edge innovations. These exhibitions act as strategic platforms for launching products and services, offering direct exposure to innovations and fostering interactions between suppliers and consumers in response to market demands. Technology spreads through the significant commercial transactions at these events, which generate substantial business volumes. This impact can be measured through the transaction volumes recorded in key trade fairs, such as, Agrishow (International Trade Fair of Agricultural Technology in Action, R$ 13.771.67 million), Bahia Farm Show (Northeast Brazil's largest agribusiness fair, R$ 10.988.29 million), Tecnoshow Comigo (Technology and Business Exhibition for Agribusiness, R$ 9.368.95 million), Expointer (International Fair of Livestock, Machinery, Equipment, and Agricultural Products, R$ 8.164.99 million), Expodireto Cotrijal (Focused on agribusiness technology and innovation, R$ 7.862.87 million), Show Rural Coopavel (One of Brazil’s most traditional agricultural fairs, R$ 6.068.28 million), Agrobrasília (A major fair in Brazil’s central region, R$ 5.044.50 million), Farm Show - MT (Agribusiness Trade and Innovation Fair of the State of Mato Grosso, R$ 4.310.51 million), Agrobalsas (Agrotechnology and business fair in Maranhão, R$ 3.985.16 million), Femec (Agribusiness Fair of the State of Minas Gerais, R$ 2.287.07 million), Mercoagro (International Trade Fair for Meat Processing and Industrialization, R$ 1.022.18 million), and Avesui (Latin American Poultry, Swine, and Fish Industry Fair, R$ 902.79 million). To achieve its objectives, this dissertation is divided into five chapters. The first chapter presents the theoretical foundations for the study. The second chapter examines the relationship between agriculture and industry from a broader perspective, using the agri-food sector as an analytical framework. The third chapter outlines a global and, more specifically, a Brazilian overview of trade fairs and exhibitions, identifying the main fairs associated with the country’s agri-food sector. The fourth and fifth chapters provide a characterization, analysis, and discussion of the spatial, historical, and economic dynamics of the sixteen most significant agri-food exhibitions in Brazil, namely: Agrishow, Agrobrasília, Agrobalsas, Bahia Farm Show, Expodireto Cotrijal, Expointer, Farm Show - MT, Femec, Show Rural Coopavel, Tecnoshow Comigo, Anuga Select Brazil, Fispal Food Service, Fispal Tecnologia, TecnoCarne, Avesui, and Mercoagro. This research highlights the role of these events as key drivers of technological innovation and diffusion, as well as their strong connections with cooperatives and financial institutions. Moreover, the study reveals the rise in commercial transactions and the rapid growth of these events in the post-pandemic period. Additionally, it identifies how these fairs align with the primary agribusiness supply chains, the expansion of agribusiness into Brazil’s Central-West region and the Matopiba area, and the ways in which they adapt to the productive transformations of their respective regions.